2020
DOI: 10.1186/s13024-020-00389-1
|View full text |Cite
|
Sign up to set email alerts
|

FRET-based Tau seeding assay does not represent prion-like templated assembly of Tau filaments

Abstract: Tau aggregation into amyloid fibers based on the cross-beta structure is a hallmark of several Tauopathies, including Alzheimer Disease (AD). Trans-cellular propagation of Tau with pathological conformation has been suggested as a key disease mechanism. This is thought to cause the spreading of Tau pathology in AD by templated conversion of naive Tau in recipient cells into a pathological state, followed by assembly of pathological Tau fibers, similar to the mechanism of nucleated polymerization proposed for p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 85 publications
1
25
1
Order By: Relevance
“…In addition, our findings provide clarity for a controversy surrounding the tau biosensor cell line. In particular, a recent study demonstrated that GFP interferes with the in vitro assembly of recombinant tau due to steric hindrance ( Kaniyappan et al, 2020 ), leading the authors to speculate that the presence of fluorophore tags would similarly perturb tau assembly in cell models, questioning the interpretation of changes in FRET signal in the biosensor cell line used in the current study. Moreover, the authors note the inefficient induction of FRET by purified tau assemblies in comparison with tissue lysates indicate that factors other than tau may be responsible for inducing FRET in biosensor cells, such as cytokines ( Kaniyappan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In addition, our findings provide clarity for a controversy surrounding the tau biosensor cell line. In particular, a recent study demonstrated that GFP interferes with the in vitro assembly of recombinant tau due to steric hindrance ( Kaniyappan et al, 2020 ), leading the authors to speculate that the presence of fluorophore tags would similarly perturb tau assembly in cell models, questioning the interpretation of changes in FRET signal in the biosensor cell line used in the current study. Moreover, the authors note the inefficient induction of FRET by purified tau assemblies in comparison with tissue lysates indicate that factors other than tau may be responsible for inducing FRET in biosensor cells, such as cytokines ( Kaniyappan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 87%
“…In particular, a recent study demonstrated that GFP interferes with the in vitro assembly of recombinant tau due to steric hindrance ( Kaniyappan et al, 2020 ), leading the authors to speculate that the presence of fluorophore tags would similarly perturb tau assembly in cell models, questioning the interpretation of changes in FRET signal in the biosensor cell line used in the current study. Moreover, the authors note the inefficient induction of FRET by purified tau assemblies in comparison with tissue lysates indicate that factors other than tau may be responsible for inducing FRET in biosensor cells, such as cytokines ( Kaniyappan et al, 2020 ). However, our observation that purified AD tau core filaments and AD tau core-induced full-length tau filaments both promote significant increases in FRET positivity in the tau biosensor cell line clearly indicates the response is mediated by tau, with a higher FRET signal associated with more aggregation-prone forms of tau, consistent with the idea that FRET is an indication of seeding activity in this cell model.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The addition of liposomes (lipofectamine) to facilitate the transduction of seeds into cells greatly increases the sensitivity of the biosensor assay but bypasses tau uptake mechanisms and therefore does not reflect seeding as it happens in the brain. A recent report suggests that the fusion of tau RD to fluorescent proteins may induce steric hindrance that avoids the elongation of tau aggregates into paired helical filaments ( Kaniyappan et al, 2020b ). The authors propose that the increase of FRET signal after exposure to seed-competent tau may result from cellular processes different from aggregation.…”
Section: Cell-based Assaysmentioning
confidence: 99%